Advances in human performance and cognitive engineering research. Vol. 1 - Salas, Eduardo (Emerald, 2001)
This volume launches a series that will focus on providing chapters that advance our understanding of human performance in organizational systems as cognitive engineering principles are applied. Topics addressed in this volume include: a historical review of a cognitive engineering research at a national laboratory; an adaptive learning system approach to designing an integrated-embedded training system; application of PRONET, a method that provides a useful representation of sequences of behaviour in a human-machine interaction; application of CTA, a method to explain the mental processes involved in performing a task; application of human performance modelling technologies in system design and evaluation; a review of training critical thinking skills that individuals and teams require in changing environments; a review of commercial simulations for team research; and research paradigms for human performance research in complex systems.
Keywords: Technology & Engineering -- Industrial Design -- General.; Psychology -- Industrial & Organizational Psychology.; Cybernetics & systems theory.; Cognition & cognitive psychology.; Human engineering.; Cognitive science.; Human-machine systems.; elektronické knihy; electronic books